PENGGUNAAN BAHAN AJAR IPA TERPADU TEKANAN DAN SISTEM PERNAPASAN UNTUK MENINGKATKAN LITERASI SAINTIFIK SISWA KELAS VIII SMP NEGERI 8 PADANG - Arnelli Amril (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The integrated science learning is required in the lessons according to the curriculum mandate of 2013. The reason is that all natural phenomena that occur can not be separated, but are a unity. In addition, the integration of scientific literacy in learning needs to be done to improve student learning outcomes. The fact that happened in school shows that integrated science learning has not been applied optimally and the value of scientific literacy test is still low. One solution that can be done is to apply scientifically integrated science-filled teaching materials. The purpose of this study was to determine the students 'scientific literacy and students' cognitive learning outcomes in science learning using integrated materials of pressure materials and respiratory system. The research includes classroom action research (PTK) with two cycles. Each cycle consists of four meetings. The subjects of the study were students of class VIII.B SMPN 8 Padang totaling 28 people. The instruments used in this study are the learning test sheets, the scientific concept appraisal sheets, the scientific process assessment sheets, and the scientific context appraisal sheets. Data analysis techniques used are descriptive statistical analysis, percentage method and graph technique. Based on data analysis that has been done can be presented two research results. First, the application of integrated teaching materials of pressure materials and respiratory system can increase students' scientific literacy in learning. This is evident from the improvement of three aspects of scientific literacy from the first cycle to the second cycle: scientific concepts, scientific processes, and scientific contexts. Second, students' cognitive learning outcomes increase from the first cycle with an average score of 75.36 to the second cycle with an average grade of 88.57. This suggests the use of integrated science materials of pressure and respiratory system in science teaching in schools can improve students' cognitive learning outcomes.